Criterion for âAnti-ShÄ«âa Approachâ, Rulings and Effects Governed over the Anti-ShÄ«âas in ImÄmÄ« Jurisprudence - Ã˜ÂªÃ™ÂˆÃ™Â„Ã˜Â§Ã›ÂŒÃ›ÂŒ, Ã˜Â±Ã˜ÂÃ™Â…Ã˜Âª; Ã™Â†Ã™Â‚Ã›ÂŒÃ˜Â¨Ã›ÂŒ, Ã˜Â³Ã›ÂŒÃ˜Â¯ Ã˜Â§Ã˜Â¨Ã™ÂˆÃ˜Â§Ã™Â„Ã™Â‚Ã˜Â§Ã˜Â³Ã™Â… (Ã™ÂÃ™Â‚Ã™Â‡ Ã™Âˆ Ã˜Â§Ã˜ÂµÃ™ÂˆÃ™Â„)
There are five views concerning the criterion for the anti-ShÄ«âa (nÄá¹£ibÄ«) in the jurisprudential literature of the ImÄmÄ« jurists. These views include 1. Prioritizing non-Ali to Ali (A.S.); 2. Showing enmity toward followers (shÄ«âas) of Ali; 3. Absolute enmity to Ahl al-Bayt (A.S.); 4. Expressing enmity to Ahl al-Bayt (A.S.); 5. Religious devotedness to enmity toward Ahl al-Bayt (A.S.). By careful consideration of the evidences referred to in this writing, we would find out that the criterion for presuming any person as anti-shÄ«âa, is their expression of enmity toward the Ahl al-Bayt (A.S.) and religious devotedness toward it. Although from the viewpoint of the renowned majority of the jurists many rulings such as unbelief (kufr), ritual impurity (nijÄsa), etc. is directed toward nÄá¹£ibÄ«s, despite the possibility of their will to unbelief vs. belief in traditions, they cannot be considered as unbelievers (kÄfir) in its connotative meaning (unbelief vs. Islam); also, what is meant by ritual impurity of the nÄá¹£ibÄ«s is their innate malice.